1991
DOI: 10.1002/1097-0142(19910301)67:5<1294::aid-cncr2820670504>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of patients with advanced colorectal cancer with cisplatin, 5-fluorouracil, and leucovorin

Abstract: Based on in vitro studies that have demonstrated synergy between 5-fluorouracil (5-FU), leucovorin (LV), and cisplatin (CDDP) against human colon cancer cell lines, a clinical trial was initiated to determine the effects of this combination in patients with advanced unresectable colorectal carcinoma. Fifty-nine patients were enrolled in the study and 12 of them had received prior conventional 5-FU chemotherapy. Treatment consisted of 4 weekly courses of high-dose LV (200 mg/m2) administered by intravenous (IV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…For our study, we chose the LoVo Dx model because, if compared with the LoVo parental cell line, it presents a higher level of c-myb expression (Melani et al, 1991). Specifically, we investigated whether the inhibition of a growth-promoting gene such as cmyb affected the antineoplastic activity of cisplatin (CDDP), a chemotherapeutic agent widely used in the treatment of several solid human malignancies (Rosenberg, 1985), including colon carcinoma (Scheithauer et al, 1991;Rowinsky et al, 1991).…”
mentioning
confidence: 99%
“…For our study, we chose the LoVo Dx model because, if compared with the LoVo parental cell line, it presents a higher level of c-myb expression (Melani et al, 1991). Specifically, we investigated whether the inhibition of a growth-promoting gene such as cmyb affected the antineoplastic activity of cisplatin (CDDP), a chemotherapeutic agent widely used in the treatment of several solid human malignancies (Rosenberg, 1985), including colon carcinoma (Scheithauer et al, 1991;Rowinsky et al, 1991).…”
mentioning
confidence: 99%
“…We have investigated the therapeutic and adverse effects of our protocol started in the early period after curative resection of stage II and III colorectal carcinoma. Scheithauer 1,10 studied a similar protocol in patients with advanced colorectal carcinomas and concluded that the protocol using three drugs, including CDDP for 4 days, showed a higher effective rate than 5‐FU/LV for 5 days, without a substantial difference in survival period.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy against advanced colorectal carcinoma using 5‐fluorouracil (5‐FU) in combination with other anticancer drugs has shown a biochemical modulation effect and has been used worldwide since the 1990 s 1–4 . Recently, CPT‐11 and oxaliplatin have become the first choice combined with 5‐FU + leucovorin (LV) for treatment of recurrent colorectal carcinoma 5,6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To inhibit TS other anticancer drugs such as cisplatin (CDDP), leucovorin (LV) and methotrexate (MTX) are introduced as modulators of the essential cofactors for ternary complex formation 4. Although several reports have described a relatively high response rate in other cancers, such as gastric cancer and colorectal cancer,5, 6 the median survival time remains extremely short in pancreatic cancer when treated with such combined chemotherapy 7, 8…”
mentioning
confidence: 99%